Assessment of the Cross-Sectional Areas of the Psoas Major and Multifidus Muscles in Patients With Adult Spinal Deformity: A Case-Control Study. Issue 7 (August 2017) - Banno, Tomohiro; Yamato, Yu; Hasegawa, Tomohiko; Kobayashi, Sho; Togawa, Daisuke; Oe, Shin; Mihara, Yuki; Kurosu, Kenta; Yamamoto, Naoto; Matsuyama, Yukihiro
Abstract : Study Design: This is a case-control study. Objective: The present study aimed to compare the cross-sectional areas of the psoas major and multifidus muscles between elderly patients with adult spinal deformity (ASD) and age-matched and body weight–matched controls, and to evaluate the associations between the cross-sectional areas of these muscles and the severity of spinal deformity. Summary of Background Data: The study included 49 female kyphosis patients with mild scoliosis (Cobb angle <20 degrees; mean age, 70.9 y, group D). The control group (group C) included age-matched and body weight–matched female patients who underwent abdominal surgery (n=98; mean age, 71.7 y). Materials and Methods: The cross-sectional areas of the bilateral psoas majors and multifidus muscles were calculated using preoperative L4/L5 axial computed tomography images. In group D, the following spinopelvic parameters were assessed: sagittal vertical axis, pelvic tilt, pelvic incidence, lumbar lordosis, and thoracic kyphosis. The relationships between the muscle cross-sectional areas and spinopelvic parameters were evaluated. Results: The cross-sectional area of the multifidus muscle was lower in group D than in group C. However, the cross-sectional area of the psoas major muscle was not different between the 2 groups. In multiple regression analysis, the cross-sectional area of the multifidus muscle was significantly associated with all spinopelvic parameters. Conclusions: The cross-sectional area of the multifidus muscle might be lower in elderly patients with ASD than in controls. In the elderly population, the severity of sagittal spinal deformity might be correlated with the cross-sectional area of the multifidus muscle. Therefore, muscle imbalances between the flexors and extensors of the spine could participate in the pathology of ASD.